Identification of Olfactory Genes From the Greater Wax Moth by Antennal Transcriptome Analysis - Jiang, Xing-Chuan; Liu, Su; Jiang, Xiu-Yun; Wang, Zheng-Wei; Xiao, Jin-Jing; Gao, Quan; Sheng, Cheng-Wang; Shi, Teng-Fei; Zeng, Hua-Rui; Yu, Lin-Sheng; Cao, Hai-Qun (Frontiers in Physiology, 2021)
The olfactory system is used by insects to find hosts, mates, and oviposition sites. Insects have different types of olfactory proteins, including odorant-binding proteins (OBPs), chemosensory proteins (CSPs), odorant receptors (ORs), ionotropic receptors (IRs), and sensory neuron membrane proteins (SNMPs) to perceive chemical cues from the environment. The greater wax moth, Galleria mellonella, is an important lepidopteran pest of apiculture. However, the molecular mechanism underlying odorant perception in this species is unclear. In this study, we performed transcriptome sequencing of G. mellonella antennae to identify genes involved in olfaction. A total of 42,544 unigenes were obtained by assembling the transcriptome. Functional classification of these unigenes was determined by searching against the Gene Ontology (GO), eukaryotic orthologous groups (KOG), and the Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. We identified a total of 102 olfactory-related genes: 21 OBPs, 18 CSPs, 43 ORs, 18 IRs, and 2 SNMPs. Results from BLASTX best hit and phylogenetic analyses showed that most of the genes had a close relationship with orthologs from other Lepidoptera species. A large number of OBPs and CSPs were tandemly arrayed in the genomic scaffolds and formed gene clusters. Reverse transcription-quantitative PCR results showed that GmelOBP19 and GmelOR47 are mainly expressed in male antennae. This work provides a transcriptome resource for olfactory genes in G. mellonella, and the findings pave the way for studying the function of these genes.